2014
DOI: 10.1159/000357291
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blood Glucose and pCO<sub>2</sub> on Spectral EEG of Premature Infants during the First Three Days of Life

Abstract: Background: Spectral EEG analysis using automated quantification of total absolute band power (tABP) expresses brain function. We hypothesized that pCO2 or blood glucose affects tABP during the critical first days of life in premature infants. Objective: To use automated tABP quantification to determine whether EEG background activity in premature infants during the first 3 days of life is influenced by pCO2 or blood glucose levels. Methods: Preterm infants, group 1 [gestational age (GA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We refer to previously published papers for more details regarding the study population and EEG technique. 19 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…We refer to previously published papers for more details regarding the study population and EEG technique. 19 , 20 …”
Section: Methodsmentioning
confidence: 99%
“…Various authors have demonstrated the effects of CO 2 on EEG activity, such as appearance of delta waves, which is a hallmark of slow wave sleep and deep anesthesia. [9][10][11][12] Otherwise, acute hypercapnia causes significant alpha and beta wave power diminution, whereas theta waves remain unchanged. 11,13 The EEG expression of hypercapnia could be the consequence of CO 2 narcotic properties or hypercapnia-induced neurologic abnormalities, such as intracerebral pH depression and extracellular adenosine augmentation, which has been shown to inhibit the synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EEG measurements were performed after the first 72h. Recent reports show that EEG dynamics changes substantially over the first 72h after birth (Schumacher et al, 2014;Victor et al, 2005b, West et al, 2006. In this study, EEG measurements were performed after the first 72h in order to have stable brain dynamics at the respective age groups.…”
Section: Discussionmentioning
confidence: 99%